Home environment in relation to allergic rhinitis among preschool children in Beijing, China: A cross-sectional study. (November 2015) - Wang, Lifang; Qu, Fang; Zhang, Yinping; Weschler, Louise B.; Sundell, Jan
Abstract: The prevalence of allergic rhinitis (AR) among children has increased markedly in Beijing during the last two decades. The purpose of this study was to estimate the prevalence of AR and to identify indoor risk factors for AR among preschool children. A cross-sectional questionnaire survey was conducted in Beijing, 2011. Parents of 5388 3–6 years old children (65% response rate) from randomly selected kindergartens in Beijing participated in this study. A Chi-square test and multiple logistic regressions were used to identify risk factors. Our survey found that the prevalences of "AR symptoms ever, " "AR symptoms current" (AR symptoms in the last 12 months) and "doctor-diagnosed AR" are 49.5%, 45.6% and 7.8%, respectively. Confounding factors for "AR symptoms" and/or "doctor-diagnosed AR" are gender, age, family allergic history, breastfeeding and current environmental tobacco smoke (ETS). New furniture, condensation on window pane and cockroaches are risk factors for both "AR symptoms ever" and "AR symptoms current". Risk factors for "AR symptoms ever" include the use of humidifier and incense. A risk factor for "AR symptoms current" is mosquitoes/flies. Risk factors for "doctor-diagnosed AR" include living close to a main road or highway, visible mold spots and current pet keeping. A protective factor against doctor-diagnosed AR is opening the child's bedroom window in winter (aOR 0.66, 95% CI 0.48, 0.92). We found that the greater the number of home environmental risk factors, the higher risk of AR. A number of home environmental factors are associated with AR among preschool children. Highlights: The prevalence of doctor-diagnosed AR among preschool children in Beijing is 7.8%. A number of home environmental factors are associated with children's AR. The greater number of home environmental risk factors, the higher likelihood of AR. Opening the child's bedroom window in winter is protective against AR.